Evaluation of the Implementation of Fixed Assets Accounting at the North Sumatra DJKN Regional Office based on PSAP No.07 about Fixed Assets Accounting - Iman Harris Wijaya T.; Anggi Pratama; Oktarini Khamilah (Budapest International Research and Critics University, 2022)
Fixed Assets is one of the important components in the balance sheet that plays a significant role in policy making in government institutions. Therefore, the recording and reporting of fixed assets must comply with government accounting standards. This study aims to evaluate the application of fixed asset accounting at the North Sumatra DJKN Regional Office based on PSAP No. 07 about Fixed Assets Accounting. The method used in this study is a qualitative approach with descriptive analysis that compares the suitability of the application of fixed asset accounting with government accounting standards. Data was collected through interviews and supporting report documentation. The results showed that the North Sumatra DJKN Regional Office had carried out the administration of fixed assets in accordance with PSAP No. 07 about Fixed Assets Accounting but with the finding of errors in the recording of fixed assets of Buildings that should have been transferred to other asset posts and the value of assets that have been discontinued from government operations which are still recorded even though the assets have been disposed of. The North Sumatra DJKN Regional Office is recommended to follow up on recording errors by reclassifying assets and making reports related to recording errors in the application system.